Controlling Preferences for Lotteries on Units of Experimental Exchange - Berg, Joyce E.; Daley, Lane A.; Dickhaut, John W.; O'Brien, John R. (Quarterly Journal of Economics, 1986)
In an experimental setting when outcomes are stochastically related to actions, predictions of equilibrium behavior depend not only on the participants' preference orderings of outcomes, but also on their orderings of lotteries on outcomes as well. We introduce and test a reward structure that can be utilized in any experimental setting to allow the experimenter to decree beforehand the subjects' preferences for lotteries on experimental outcomes. We show analytically that the proposed reward structure can induce subjects to behave as if they have the decreed preference function defined on experimental outcomes. Empirical tests using two different choice settings provide evidence to support this ability to control preferences.